Electrode composition for electrospinning
Patent Information
- Application Number
- CN202280040045.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-09
- Filing Date
- 2022-04-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-04-11
AI Technical Summary
然而,这些方法只能将电极线宽和电极间的间距实现为40μm至80μm的水平,因此使用这些方法难以形成更小且更精确的精细图案
[0028]根据本发明的用于电喷射的电极组合物适合于通过电喷射实现具有优异厚度均匀性的超薄电极图案。另外,所实现的电极可以具有优异的电导率。此外,其可以适合于在如生片等的陶瓷片上形成电极。另外,当将所形成的电极与陶瓷生片共烧结时,烧结体的形状可以保持完整,还可以防止烧结体的层间分离。此外,由于可以实现超薄电极,因此可以广泛用作高层叠化的多层陶瓷部件的内部电极。
Smart Images

Figure CN117678039B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an electrode composition, and more specifically, to an electrode composition for electro-jetting. Background Technology
[0002] Among the electronic components widely used in electronic devices, condensers, capacitors, varistors, suppressors, and MLCCs (Multi-Layer Ceramic Capacitors) are essentially co-sintered multilayer ceramic components achieved by stacking several to hundreds of green sheets printed with electrode patterns, and then co-sintering the electrodes and green sheets together. Recently, driven by the miniaturization and high performance requirements of electronic devices, extensive research is underway to achieve both miniaturization and high capacitance for these components.
[0003] In the case of such co-sintered multilayer ceramic components, in order to achieve high capacity, in addition to improving the materials of the dielectric and electrodes constituting the green sheets, it is also attempted to achieve high-layer stacking by stacking more green sheets. To achieve high-layer stacking of co-sintered multilayer ceramic components, it is necessary to reduce the thickness of the green sheets corresponding to the dielectric and the electrode patterns, and, in order to miniaturize, the electrode linewidth of the electrode patterns and the spacing between the electrodes must be refined.
[0004] On the other hand, existing methods for printing electrode patterns on raw sheets use screen printing or gravure printing, which have the advantage of low cost. However, these methods can only achieve electrode linewidths and inter-electrode spacing at the level of 40 μm to 80 μm, making it difficult to form smaller and more precise fine patterns. Furthermore, because the printed electrode thickness is approximately 5 μm to 100 μm, it is difficult to form ultra-thin electrode patterns of less than 1 μm. Therefore, using existing screen printing or gravure printing makes it difficult to form internal electrodes for multilayered and miniaturized co-sintered ceramic components with high-level stacking. In addition, to print ultra-thin electrodes, the viscosity of the electrode composition used for printing needs to be significantly reduced, but this leads to problems with ink bleeding and reduced printing resolution.
[0005] Therefore, in recent years, inkjet printing has been continuously used to achieve finely patterned electrodes. When inkjet printing is used to form electrodes, ultra-thin electrode patterns with a thickness of less than 1μm can be achieved. However, the productivity is low, the cost of ink used to manufacture electrodes is high, and there is also the problem that it is not easy to print electrode patterns on large-area raw films.
[0006] Therefore, there is an urgent need to develop a method for easily and inexpensively forming ultrathin electrode patterns on large-area green sheets, as well as electrode compositions suitable for this method. Summary of the Invention
[0007] Technical issues
[0008] The present invention was developed in view of the above-mentioned problems, and its object is to provide an electrode composition for electro-spraying suitable for printing ultra-thin electrode patterns with excellent thickness uniformity on ceramic sheets such as green sheets using an electro-spraying method.
[0009] Another object of the present invention is to provide an electrode composition for electro-spraying that, while achieving an electrode with excellent electrical conductivity, can prevent deformation of the sintered body shape or interlayer separation due to differences in shrinkage characteristics that occur during co-sintering after printing on a ceramic sheet such as a green sheet.
[0010] Solution to the problem
[0011] To address the aforementioned problems, the present invention provides an electrode composition for electro-spraying, which is an electrode composition for achieving an electrode with an average thickness of less than 1 μm during drying. The electrode composition for electro-spraying comprises conductive metal powder, ceramic powder, binder resin, and solvent with an average particle size of less than 150 nm.
[0012] According to one embodiment of the present invention, the electrode composition for electro-jetting described above can be an electrode composition for realizing internal electrodes of multilayer ceramic components.
[0013] Furthermore, the average particle size of the aforementioned conductive metal powder can be below 80 nm.
[0014] Furthermore, in the aforementioned conductive metal powder, the number of particles with a diameter more than twice the average particle size can be less than 20% of the total number of conductive metal powders, and the number of particles with a diameter less than 0.5 times the average particle size can be less than 20% of the total number of conductive metal powders.
[0015] In addition, the aforementioned conductive metal powder may include at least one metal selected from the group consisting of Ni, Mn, Cr, Al, Ag, Cu, Pd, W, Mo and Co, an alloy containing at least one of them, and a mixed metal containing at least two of them.
[0016] Furthermore, the ceramic powder may have an average particle size that is 0.1 to 0.5 times the average particle size of the conductive metal powder.
[0017] In addition, the aforementioned ceramic powder may include at least one ceramic powder selected from the group consisting of titanium dioxide, alumina, silicon dioxide, cordierite, mullite, spinel, barium titanate, and zirconium oxide.
[0018] Furthermore, the content of the aforementioned conductive metal powder can be from 10% to 30% by weight, based on the total weight.
[0019] Furthermore, the content of the aforementioned ceramic powder can be from 4 to 10 parts by weight relative to 100 parts by weight of conductive metal powder.
[0020] Furthermore, the content of the aforementioned adhesive resin relative to 100 parts by weight of conductive metal powder can be from 2 parts by weight to 13 parts by weight.
[0021] Furthermore, the average particle size of the aforementioned ceramic powder can be below 45 nm.
[0022] In addition, the aforementioned adhesive resin may comprise 30 to 60 parts by weight of ethyl cellulose relative to 100 parts by weight of polyvinyl butyral.
[0023] Furthermore, the viscosity at 25°C can range from 50 cps to 150 cps.
[0024] Furthermore, the present invention provides an electro-spraying electrode, which is an electrode dried after electro-spraying an electrode composition according to the present invention onto a predetermined area, having an average thickness of less than 1 μm.
[0025] Furthermore, according to one embodiment of the present invention, the thickness uniformity can be less than 10%.
[0026] Furthermore, the present invention provides a multilayer ceramic component comprising an internal electrode formed by sintering an electro-spraying electrode according to the present invention.
[0027] The effects of the invention
[0028] The electrode composition for electro-spraying according to the present invention is suitable for achieving ultrathin electrode patterns with excellent thickness uniformity by electro-spraying. Furthermore, the achieved electrode can have excellent electrical conductivity. Moreover, it is suitable for forming electrodes on ceramic sheets such as green sheets. Additionally, when the formed electrode is co-sintered with the ceramic green sheet, the shape of the sintered body can be maintained, and interlayer separation of the sintered body can be prevented. Furthermore, since ultrathin electrodes can be achieved, it can be widely used as internal electrodes in multilayer ceramic components with high-level stacking. Attached Figure Description
[0029] Figure 1 This is an SEM image of nickel powder with an average particle size of 75 nm, which is included as a conductive metal powder in one embodiment of the present invention.
[0030] Figure 2 for Figure 1 SEM image of nickel powder before wet classification.
[0031] Figure 3 This is an SEM image of barium titanate powder, which is included as a ceramic powder in one embodiment of the present invention.
[0032] Figure 4 and Figure 5 Each contains Figure 1 and Figure 2 A photograph of an electrode composition for electrospraying of nickel powder, wherein, Figure 4 This is a photograph showing that nickel powder and ceramic powder are uniformly dispersed without any sediment. Figure 5 This is a photograph showing phase separation that occurs between nickel powder and ceramic powder due to nickel powder precipitation.
[0033] Figure 6 and Figure 7 The images are optical microscope photographs of electrodes dried after electro-jet processing of the electrode composition used for electro-jet processing. Figure 6 A photograph of an electrode pattern with excellent surface formation properties, showing a continuous electrode pattern without any unformed electrode areas. Figure 7 This is a photograph of an electrode pattern where the continuous electrode surface is partially not formed due to the presence of unformed portions (circled portions) within the electrode pattern.
[0034] Figure 8 and Figure 9 An optical microscope image of an electrode after drying following electro-jet printing of an electrode composition used for electro-jet printing, wherein, Figure 8 A photograph of an electrode pattern with excellent surface formation properties, showing a continuous electrode pattern without any unformed electrode areas. Figure 9 This is a photograph of an electrode pattern where the continuous electrode surface is partially not formed due to the presence of detached electrode portions that do not form electrodes within the electrode pattern. Detailed Implementation
[0035] The best way to implement the invention
[0036] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings, so that those skilled in the art can easily implement the present invention. The present invention can be implemented through various different methods and is not limited to the embodiments described in this specification.
[0037] The electrode composition according to an embodiment of the present invention is suitable for electrospraying and can achieve an ultrathin electrode with an average thickness of 1.0 μm or less, preferably 0.6 μm or less, during drying. It is achieved by comprising conductive metal powder with an average particle size of 150 nm or less, ceramic powder, binder resin, and solvent. Furthermore, the above-described electrode composition is suitable for forming electrodes on green sheets and can achieve ultrathin electrodes, thus it may be particularly suitable for realizing internal electrodes in multilayer ceramic components such as MLCCs that require high-layer stacking.
[0038] The aforementioned conductive metal powder imparts conductivity and forms the electrode body after sintering. Any conductive metal powder commonly used in the manufacture of electrodes for electronic components can be used without restriction. As an example, the conductive metal powder may include at least one metal selected from the group consisting of nickel, manganese, chromium, aluminum, silver, copper, palladium, tungsten, molybdenum, and cobalt; an alloy containing at least one of these metals; and a mixed metal containing at least two of these metals. However, considering the sintering temperature during co-sintering with ceramic green sheets, the conductive metal powder may include at least one selected from the group consisting of palladium, silver-palladium alloys, silver, nickel, and copper. Preferably, considering heat resistance, conductivity, and material cost, nickel may be included.
[0039] Furthermore, the average particle size of the aforementioned conductive metal powder can be less than 150 nm, preferably less than 100 nm, and more preferably less than 80 nm. If the average particle size of the conductive metal powder exceeds 150 nm, the thickness of the electrode dried after electrospraying will exceed 1 μm, or it will be difficult to form a continuous electrode surface. Even if a dried electrode with a thickness of 1 μm is achieved, the thickness uniformity may be very poor, making it difficult to achieve high-quality multilayer ceramic components with stacked layers. On the other hand, the average particle size of the conductive metal powder can be 5 nm or more, preferably 10 nm or more, and more preferably 20 nm or more. If the average particle size is less than 5 nm, the conductive metal powder itself is not easy to produce, and the material cost may also increase. In addition, as the metal powder becomes finer, it is necessary to ensure dispersibility. However, since organic compounds such as dispersants added to ensure dispersibility may not be easily degreased, separation may occur between the green layers during the sintering of multilayer ceramic components. Furthermore, if a separate dispersant is not included, the dispersibility decreases when the average particle size of the conductive metal powder is too small, and it aggregates to form coarse secondary particles, making it difficult to form a continuous electrode surface in the achieved dry electrode, and the thickness unevenness becomes serious, so it is not preferred.
[0040] Furthermore, the aforementioned conductive metal powder can have a particle size distribution such that the number of particles with a diameter more than twice the average particle size is less than 20% of the total number of conductive metal powders, preferably less than 15% of the total number of conductive metal powders, more preferably less than 10% of the total number of conductive metal powders, and even more preferably less than 5% of the total number of conductive metal powders; and the number of particles with a diameter less than 0.5 times the average particle size is less than 20% of the total number of conductive metal powders, preferably less than 10% of the total number of conductive metal powders. This minimizes secondary particles formed by the aggregation of conductive metal powder in the electrode composition supplied for electro-spraying, and is suitable for minimizing or preventing the deposition of conductive metal powder in the spinning solution chamber of the electro-spraying device. This facilitates the formation of a continuous electrode surface in the dry electrode where there are no areas of the unsprayed electrode composition where the electrode is partially absent. It also helps prevent deterioration of the electrode appearance quality, such as uneven electrical properties (resistivity, etc.) at each location of the electrode formed by electro-spraying or uneven electrode thickness.
[0041] Furthermore, based on the total weight of the electrode composition, the content of the conductive metal powder can be less than 30% by weight, preferably from 10% to 30% by weight, and more preferably from 20% to 30% by weight. If the content of the conductive metal powder exceeds 30% by weight, the conductive metal powder in the electrode composition supplied for electro-spraying may settle or precipitate, which may result in uneven spraying of the conductive powder during electro-spraying. Additionally, it may be difficult to adjust the thickness of the electrode achieved by electro-spraying. Furthermore, if the content of the conductive metal powder is less than 10% by weight, the dried or sintered electrode produced by electro-spraying may form teardrop-shaped islands, thereby making it difficult to achieve the desired electrode, for example, reducing the continuity of the electrode surface or causing uneven thickness of the dried electrode.
[0042] On the other hand, due to the aforementioned conductive metal powder, the electrode composition has high electrical conductivity, which may make electro-spraying difficult. Therefore, the electrode composition includes ceramic powder, thereby adjusting the conductivity of the electrode composition to a level suitable for electro-spraying. Furthermore, it prevents shape deformation such as flattening of the sintered body caused by sintering temperature differences between the electrode and the green sheet and the resulting differences in shrinkage characteristics during co-sintering after processing the electrode composition on the green sheet. Moreover, after sintering, the ceramic component derived from the ceramic powder moves towards the surface of the sintered electrode, undergoing delamination with the conductive component derived from the sintered conductive metal powder, thus increasing the dielectric constant and contributing to improved properties of multilayer ceramic components such as MLCCs.
[0043] Furthermore, the average particle size of the aforementioned ceramic powder can be less than 100 nm; for example, it can be less than 70 nm, less than 45 nm, or even 1 nm to 30 nm. Additionally, considering the average particle size of the conductive metal powder, ceramic powder with an appropriate average particle size can be used. Specifically, ceramic powder with an average particle size of less than 0.5 times, preferably less than 0.3 times, the average particle size of the conductive metal powder can be used, which is beneficial for delaying the shrinkage of the electrode compared to the green sheet during sintering. For example, when using conductive metal powder with an average particle size of 80 nm, the average particle size of the ceramic powder can be less than 20 nm. However, if the average particle size of the ceramic powder is equal to or less than 0.1 times the average particle size of the conductive metal powder, the increased particle surface area may necessitate an increase in the amount of resin added, and may also lead to uneven thickness of the dried and / or sintered electrode, and an increased electrode shrinkage rate during sintering, which is therefore undesirable.
[0044] On the other hand, the smaller the proportion of coarse particles with a particle size equal to or greater than twice the average particle size in the ceramic powder, the more beneficial it is to maintain a uniform dispersed phase. Therefore, in the above-mentioned ceramic powder, the number of particles with a particle size of more than twice the average particle size can be 20% or less of the total number of ceramic powder particles, preferably 10% or less, and more preferably 5% or less.
[0045] Furthermore, any known ceramic powder can be used without restriction as the ceramic powder mentioned above. For example, the ceramic powder may include at least one ceramic powder selected from the group consisting of titanium dioxide, alumina, silicon dioxide, cordierite, mullite, spinel, barium titanate, and zirconium oxide. In this case, when the ceramic powder is used to form an internal electrode by electro-spraying an electrode composition onto a green sheet, a composition with the same dielectric composition as the green sheet can be selected. This allows for easier control of the shrinkage characteristics between the green sheet and the electrode during co-sintering, and also helps improve the adhesion and bonding properties between the electrode and the green sheet. On the other hand, when the ceramic powder is barium titanate, Ca and Zr are partially dissolved in (Ba... 1- x Ca x TiO3, Ba(Ti 1-y Ca y O3、(Ba 1-x Ca x (Ti) 1-y Zr y )O3 or Ba(Ti 1-y Zr y O3 and other substances also fall under the category of barium titanate.
[0046] Furthermore, the content of the ceramic powder relative to 100 parts by weight of conductive metal powder can be from 4 to 10 parts by weight, preferably from 4 to 7 parts by weight. If the content of the ceramic powder is less than 4 parts by weight, it is difficult to adjust the thickness of the resulting electrode. Additionally, when co-sintering with the ceramic green sheet, it is difficult to control the shrinkage characteristics, and the resulting electrode may frequently crack and peel off after sintering. Furthermore, if the content of the ceramic powder exceeds 10 parts by weight, the conductivity of the resulting electrode decreases, and the degree of electrode shrinkage during sintering may increase excessively.
[0047] On the other hand, in this invention, the particle size of the conductive metal powder and ceramic powder is based on particle size determination by dynamic light scattering, and is volume-based. The average particle size refers to the particle size corresponding to D50 in the cumulative volumetric particle size distribution. Furthermore, the aforementioned measuring device can be any known measuring device capable of measuring and counting nanoscale powder particle sizes, such as the Zetasizer series or APS-100 measuring devices.
[0048] Furthermore, dry plasma powder synthesis methods such as PVD and CVD can achieve conductive metal powders with an average particle size of less than 150 nm, which is beneficial for preparing powders with clean particle surfaces. Additionally, wet classification processes using known natural fall-off methods or centrifugation, applied to the conductive metal powders obtained by dry plasma powder synthesis methods, may be beneficial for obtaining conductive metal powders with the desired particle size and distribution. In this case, forced classification by centrifugation is preferred, and for production efficiency, a continuous centrifuge is preferred. The average particle size of the aforementioned continuous centrifuge can be adjusted by regulating the centrifuge speed and feed rate per minute, causing the conductive metal powder in the electrode composition to settle rapidly. This allows for the control of a smaller proportion of coarse particles that hinder uniform dispersion, such as conductive metal powder with a particle size more than twice the average particle size. If the centrifuge speed is too high, the yield is greatly reduced; if the centrifuge speed is too low, the removal rate of coarse particles that hinder uniform dispersion is reduced. Furthermore, if the feed volume is too large, the time the powder is subjected to centrifugal force in the centrifuge chamber is shortened, making it difficult to remove macroscopic particles. If the feed volume is too small, although efficiency is improved, the production time increases, which is not preferable. Additionally, a filtration process can be performed to precisely control the particle size distribution of the conductive metal powder to the desired level. In this case, the filtration process can be performed using conventional processes that remove coarse particles using known filter media; therefore, there are no particular limitations in this invention. Specifically, Figure 1 SEM images of the conductive metal powder used in Example 4, by means of... Figure 2 The conductive metal powder shown is controlled to have a low ratio of coarse particles through wet classification using centrifugal separation. Therefore, as... Figure 4 As shown, the electrode composition is well dispersed. On the other hand, when there are many coarse particles in the conductive metal powder, such as... Figure 5 As shown, it can be confirmed that a large amount of conductive metal powder precipitates to separate from the ceramic powder phase.
[0049] Furthermore, the aforementioned ceramic powder can be prepared with the desired particle size distribution using commercially available ceramic powders and appropriate known powder technology and fine particle control technology. Specifically, it can be prepared using various known pulverizing and classifying methods, related apparatus, and by adjusting pulverizing conditions, pulverizing time, and other factors. For example, in the case of a pulverizer, any of the following can be used: a mechanical pulverizer using a blade mill or a super rotor, or an air jet mill that uses a high-speed airflow of high-pressure air to pulverize particles by colliding them with the wall. Alternatively, the pulverization level can be adjusted by re-feeding the pulverized material to another pulverizer for further pulverization. In addition, the ceramic powder can be classified using a classifier such as a centrifugal disperser to classify the pulverized material, a disperser that uses physical dispersing forces such as high-speed airflow to prevent fine particle agglomeration, or a wet classification method using centrifugation to achieve the desired particle size distribution. Detailed descriptions of these methods are omitted in this invention.
[0050] In addition to the aforementioned conductive metal powder and ceramic powder, the electrode composition also includes a binder resin, thereby exhibiting electrode formation properties through electro-spraying and adhesion characteristics to the electro-sprayed surface. As the binder resin, any binder resin commonly used in conventional electrode compositions is acceptable, such as polyvinyl butyral, polyvinyl butyral, polyvinyl alcohol, acrylic resins, epoxy resins, phenolic resins, alkyd resins, cellulose polymers, and rosin resins. However, considering the printability of the electrode through electro-spraying and the adhesion and bonding to the electro-sprayed surface, particularly the green sheet surface, a binder resin prepared by mixing polyvinyl butyral and ethyl cellulose can be used. In this case, the binder resin may contain 30 to 60 parts by weight of ethyl cellulose per 100 parts by weight of polyvinyl butyral, thereby achieving even better printability and surface adhesion characteristics. If the ethyl cellulose content exceeds 60 parts by weight, the size of the slurry particles ejected from the nozzle during electro-spraying may not be refined, and the dried electrode film after electro-spraying becomes too hard, reducing the adhesion to the electro-sprayed surface, and electrode peeling may occur on the sprayed surface during sintering. Furthermore, if the ethyl cellulose content is less than 30 parts by weight, the printability of the electrode by electro-spraying may be reduced.
[0051] Furthermore, preferably, the weight-average molecular weight of polyvinyl butyral and ethyl cellulose is less than 100,000, for example, from 10,000 to 100,000, thereby making it easy to achieve a viscosity suitable for electrospraying. If the weight-average molecular weight exceeds 100,000, electrospraying may become difficult due to the excessive increase in viscosity.
[0052] Furthermore, relative to 100 parts by weight of conductive metal powder, the content of the binder resin can be 13 parts by weight or less, preferably 10 parts by weight or less, and more preferably 2 to 10 parts by weight. If the content of the binder resin exceeds 13 parts by weight, cracks may appear in the electrode during sintering, or separation may occur between the stacked green sheet layers when sintered together with the green sheet. Additionally, if the content of the binder resin is less than 2 parts by weight, the metal powder or ceramic powder in the electrode composition may settle or its dispersibility may decrease, and the electrode may peel off from the sprayed surface before drying and sintering after spraying.
[0053] Furthermore, the aforementioned electrode composition includes a solvent. As for the solvent, it can be any solvent suitable for use in known electrode compositions that can be used in the spray solution during electro-spraying without affecting the surface to be electro-sprayed, such as green sheets, conductive metal powders, and ceramic powders, and is also capable of dissolving the binder resin. For example, at least one organic solvent such as dihydroterpineol, dihydroterpineol acetate, terpineol, octanol, n-alkanes, decanol, tridecanol, dibutyl phthalate, butyl acetate, butyl carbitol, butyl carbitol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate, isobornyl isobutyrate, ethylene glycol monobutyl ether acetate, dipropylene glycol methyl ether acetate, ethyl acetate, butyl acetate, and hexyl acetate can be used. Preferably, at least one organic solvent such as a mixture of dihydroterpineol and dihydroterpineol acetate or a mixture of dihydroterpineol acetate and ethyl acetate can be used. A mixture of dihydroterpineol and dihydroterpineol acetate is also preferred.
[0054] On the other hand, the electrode composition for electro-spraying according to an embodiment of the present invention can be realized as a photosensitive electrode composition. For this purpose, the aforementioned adhesive resin may include a photosensitive resin, and the photosensitive electrode composition may further include a monomer and a photoinitiator.
[0055] The aforementioned adhesive resin includes a photosensitive resin, which acts as a binder in the photosensitive electrode composition to maintain the adhesion of the dry electrode and to ensure solubility in the developer. The photosensitive resin can be cured to form a cured film through intermolecular cross-linking under the action of active energy such as ultraviolet light or electron beams, or it can dissolve in the developer due to the unwinding of the intermolecular cross-linking.
[0056] As the aforementioned photosensitive resin, any photosensitive resin commonly used in the field of photosensitive electrode pastes can be used without restriction. Furthermore, the aforementioned photosensitive resin can be either positive or negative. For example, the aforementioned photosensitive resin can be a photosensitive adhesive resin used in photosensitive resin compositions of acrylates, cellulose, phenolic varnishes, water-soluble polymers, polyimides, or their precursors. However, the aforementioned photosensitive resin is preferably a negative acrylate photosensitive adhesive. As the aforementioned acrylate photosensitive adhesive, resins having olefinic unsaturated bonds such as vinyl, allyl, acryloyl, and methacryloyl, or photosensitive groups such as propargyl, can be used, such as acrylic copolymers with olefinic unsaturated side chains, unsaturated carboxylic acid modified epoxy resins, or resins further containing polybasic anhydrides, etc., and various known existing photosensitive resins (photosensitive prepolymers). Specifically, the aforementioned photosensitive resin may include an acrylate copolymer formed by copolymerizing at least two monomers selected from glycidyl methacrylate (GMA), methyl methacrylate (MMA), isobornyl methacrylate (IBOMA), benzyl methacrylate, methacrylic acid (MMA), acrylic acid (AA), and styrene. As a more specific example, the aforementioned photosensitive resin may be a glycidyl methacrylate-methyl methacrylate copolymer, a glycidyl methacrylate-methyl methacrylate-isobornyl methacrylate copolymer, or a methyl methacrylate-benzyl methacrylate-methyl methacrylate copolymer.
[0057] Furthermore, the photosensitive resin according to an embodiment of the present invention is copolymerized from methacrylic acid, methyl methacrylate and isobornyl methacrylate, containing 15.5 mol% to 19.5 mol% methacrylic acid, and may include acrylate copolymers having a weight average molecular weight of 8,000 to 15,000. More preferably, it may be a copolymer containing 25 mol% to 40 mol% methyl methacrylate and the balance isobornyl methacrylate, which may be advantageous for achieving electrode patterns with excellent quality, resolution and photosensitivity and prevention of residues.
[0058] Furthermore, to adjust the acid value, the aforementioned acrylate copolymers can be introduced by reacting the carboxyl functional group in the acrylate copolymer with a compound having an epoxy or isocyanate functional group. In this case, the epoxy-containing compound can be, for example, at least one functional group selected from methylene, vinyl, and allyl functional groups at the terminal, specifically, allyl glycidyl ether. Additionally, the isocyanate-containing compound can be, for example, 2-acryloyloxyethyl isocyanate.
[0059] In addition, acrylate copolymers with adjusted acid values can have acid values from 25 mg KOH / g to 100 mg KOH / g, thereby exhibiting excellent photosensitivity and developability.
[0060] In addition, the glass transition temperature of the photosensitive resin, which is the above-mentioned acrylate copolymer, can be from 20°C to 150°C.
[0061] In addition, according to one embodiment of the present invention, besides the acrylate photosensitive resin, the photosensitive resin may also include polyimide or its precursor. In this case, the content of polyimide or its precursor may be from 10 parts by weight to 60 parts by weight relative to 100 parts by weight of the acrylate resin, which may be more advantageous in achieving the objectives of the present invention.
[0062] On the other hand, the adhesive resin containing the aforementioned photosensitive resin may also include polyvinyl butyral resin. An adhesive resin formed solely from the photosensitive resin may have poor adhesion to surfaces to be electro-sprayed, such as green sheets. Therefore, polyvinyl butyral resin may be further included to achieve improved adhesion and bonding strength to the green sheet. The content of the aforementioned polyvinyl butyral resin in the adhesive resin can be from 10% to 50% by weight. If the content exceeds 50% by weight, defects such as residues during development after exposure may increase; if the content is less than 10% by weight, the effect on improving adhesion may be minimal. In this case, considering that the electrode composition to be achieved must maintain a low viscosity, it is preferable to use the aforementioned polyvinyl butyral resin with a weight-average molecular weight of 100,000 or less; for example, it is preferable to use the aforementioned polyvinyl butyral resin with a weight-average molecular weight of 10,000 to 100,000.
[0063] Furthermore, the aforementioned monomers contain carbon double bonds. Through activation energy such as ultraviolet light or electron beams, free radicals are excited, causing the double bonds to transform into single bonds, initiating a polymerization reaction, thereby forming a cured structure in the photosensitive electrode composition. There are no particular limitations on the monomers used in the field of photosensitive pastes. For example, the monomers can be multifunctional monomers such as difunctional, trifunctional, or tetrafunctional monomers. More specifically, the multifunctional monomers can be acrylate monomers selected from trimethylolpropane triacrylate, trimethylolpropane ethoxylated triacrylate, pentaerythritol triacrylate, or pentaerythritol tetraacrylate, but are not limited to these.
[0064] Furthermore, the content of the aforementioned monomers can be from 10 parts by weight to 100 parts by weight of 100 parts by weight of photosensitive resin. If the content of the aforementioned monomers is less than 10 parts by weight, the curing density of the exposed pattern may be weakened; if the content of the aforementioned monomers exceeds 100 parts by weight, the pattern characteristics may deteriorate, and the residual organic matter after curing may lead to increased resistance or delamination between layers of stacked green sheets.
[0065] According to one embodiment of the present invention, an oligomer may also be included as a component that forms a cured structure via free radicals, similar to the monomers described above. As the oligomer, any oligomer commonly used in photosensitive electrode compositions is not limited in its use; for example, the oligomer may be an acrylate with a molecular weight of 1000 or less. Based on 100 parts by weight of the photosensitive resin described above, the content of the oligomer may be from 10 parts by weight to 100 parts by weight, but is not limited thereto.
[0066] Furthermore, the aforementioned photoinitiators are compounds that induce chemical reactions by generating free radicals when irradiated with active energy such as ultraviolet light or electron beams. There are no particular limitations as long as they are photopolymerization initiators commonly used in the field of photosensitive electrode compositions. For example, acetophenone-based compounds, benzophenone-based compounds, thioxanone-based compounds, benzoin-based compounds, triazine compounds containing monophenyl groups, oxime compounds, carbazole-based compounds, diketone compounds, sulfonium borate-based compounds, diazo compounds, and biimidazole-based compounds can be used as photoinitiators. Specifically, as the aforementioned photoinitiator, options selected from benzophenone, methyl benzoyl benzoate, 4,4′-bis(dimethylamino)benzophenone, 4,4′-bis(diethylamino)benzophenone, 4,4′-dichlorobenzophenone, 4-benzoyl-4′-methyldiphenyl ketone, dibenzyl ketone, fluorene, 2,2′-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, and 2-hydroxy 2-Methylacetone, p-tert-butyldichloroacetophenone, thioxanthone, 2-methylthioxanthone, 2-chlorothioxanthone, 2-isopropylthioxanthone, diethylthioxanthone, 4-azidobenzylacetophenone, 2,6-bis(p-azidobenzyl)cyclohexanone, 6-bis(p-azidobenzyl)-4-methylcyclohexanone, 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-propanedione-2-(o-ethoxy)oxime 1-[4-(phenylthio)-2-(o-benzoyl)oxime], 1,3-diphenyl-glycerol-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxy-glycerol-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyl oxime)], 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzene) At least one of the following groups: (formyl)-phenylphosphine oxide, michidone, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-phenylpropanone, naphthalenesulfonyl chloride, quinolinesulfonyl chloride, N-phenylthioacridone, 4,4′-azobisisobutyronitrile, diphenyl disulfide, benzothiazole disulfide, triphenylphosphine, benzopyroxene peroxide, and photoreducing pigments such as eosin and methylene blue, as well as ascorbic acid and triethanolamine.
[0067] The content of the photoinitiator can be from 1 part by weight to 50 parts by weight relative to 100 parts by weight of the adhesive resin. If the content of the photoinitiator is less than 1 part by weight, the curing density of the exposed area may be reduced, and the cured film may be affected during the development process. In addition, if the content of the photoinitiator exceeds 50 parts by weight, excessive light absorption may occur on the upper part of the dry coating film, making it difficult to form the desired pattern.
[0068] On the other hand, along with or instead of a photoinitiator, an azide-based photocrosslinking agent compound may be included. More specifically, it may include compounds with straight-chain alkylene groups having 4 to 20 carbon atoms whose ends are substituted with azide groups. Compounds as described above can crosslink without a photoinitiator, thus offering the advantage of reducing the photoinitiator content. Specific examples include 1,4-diazidobutane, 1,5-diazidopentane, 1,6-diazidohexane, 1,7-diazidoheptane, 1,8-diazidooctane, 1,10-diazidodecane, 1,12-diazidododecane, or mixtures thereof.
[0069] Furthermore, relative to 100 parts by weight of conductive metal powder, the total weight of the binder resin and monomers, including the aforementioned photosensitive resin, can be 13 parts by weight or less, preferably 10 parts by weight or less, and more preferably 2 to 10 parts by weight. If the content of the binder resin exceeds 13 parts by weight, cracks may appear in the electrode during sintering, or separation may occur between the stacked green sheet layers when sintered together with the green sheet. Additionally, if the content of the binder resin is less than 2 parts by weight, the metal powder or ceramic powder in the electrode composition may settle or its dispersibility may decrease, and the electrode may peel off from the sprayed surface before drying and sintering after spraying.
[0070] On the other hand, it should be noted that the specific type and content of the binder resin, monomer and photoinitiator including the above-mentioned photosensitive resin can be determined by comprehensively considering the manufacturing method of electro-spraying, the purpose of the internal electrodes of the multilayer ceramic component, the thickness, line width, distance between the widths of the internal electrodes to be realized, and the materials and particle size of the metal powder and ceramic powder.
[0071] In addition, the electrode composition or photosensitive electrode composition may contain additives such as dispersants, plasticizers, leveling agents, thixotropic agents, slip agents, and curing accelerators, in addition to the above-mentioned components. As for the above-mentioned additives, as long as they are known additives contained in electrode compositions, they can be used without restriction. Therefore, there is no specific limitation in this invention.
[0072] As an example, the dispersant described above is included to impart dispersion stability to metal powders and ceramic powders, and there are no particular limitations as long as it is a dispersant commonly used in electrode compositions. Preferably, as the dispersant described above, at least one selected from the group consisting of oleic acid, polyethylene glycol fatty acid esters, glyceryl esters, sorbitol esters, propylene glycol esters, glycol esters, fatty acid alkanolamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, amine oxides, and poly12-hydroxystearic acid can be used.
[0073] On the other hand, the content of additives, including the aforementioned dispersant, can be from 10 to 50 parts by weight relative to 100 parts by weight of the binder resin. If the content of additives is less than 10 parts by weight, it may be difficult to achieve the desired effect by means of additives. In addition, if the content of additives exceeds 50 parts by weight, the physical properties such as the conductivity of the electrode composition and the uniformity of the thickness of the dried electrode and / or sintered electrode achieved after spraying may be reduced.
[0074] Furthermore, the viscosity of the electrode composition containing the above-mentioned components can be from 50 cps to 150 cps, preferably from 70 cps to 100 cps, thus potentially suitable for electrospraying and beneficial for achieving ultra-thin dried electrodes after electrospraying. If the viscosity is less than 50 cps, the dispersed conductive metal powder and ceramic powder may rapidly precipitate, and the dispersibility may deteriorate. Additionally, if the viscosity exceeds 150 cps, it may be difficult to precisely control the thickness by electrospraying, and it may be difficult to manufacture electrodes with thinner thicknesses. The viscosity here is measured according to ISO 554 using a Brookfield rotational viscometer LV at 25°C, 65% relative humidity, and 10 rpm.
[0075] On the other hand, the aforementioned electrode composition can be achieved by mixing conductive metal powder, ceramic powder, binder resin, and solvent, and then dispersing the conductive metal powder and ceramic powder. In this case, a large amount of heat is generated during the mixing and dispersion process due to the finely powdered particles; therefore, using a high-pressure dispersing device or a bead mill for mixing and dispersion may be more advantageous. Furthermore, before transferring the electrode composition into the electro-spraying device and spraying it through the nozzle, it is preferable to maintain a state of maximum dispersion. For this purpose, the spray solution tank within the electro-spraying device may also include a stirring device capable of maintaining the dispersion state. This stirring device can be a known stirring device such as an impeller; in this invention, there is no specific limitation on this.
[0076] The electrode composition described above can be sprayed onto a surface to be sprayed (e.g., a ceramic green sheet) with a predetermined electrode pattern using a conventional electro-spraying device, and then formed into an electrode through a drying and sintering process. In this case, the average thickness of the electrode during drying can be achieved to be less than 1 μm, and the average thickness after sintering can be achieved, for example, to be less than 0.3 μm to 1.0 μm.
[0077] Furthermore, the electrode surface of the electrode coated and dried according to the formed pattern can have a continuous electrode surface without any uncoated areas. Additionally, since large-area processing is possible, for example, the area of a continuous electrode surface dried by electro-spraying on a ceramic green sheet with an area of 20cm × 20cm or more can be formed to be 70% or more, preferably 80% or more, and more preferably 90% or more.
[0078] Furthermore, preferably, after dividing the continuous electrode surface for measuring the thickness of the dry electrode into five non-overlapping regions, the thickness uniformity using Formula 1, which is the average of the five average thicknesses measured for each region and their standard deviation, can be within 10%, preferably within 5%, and more preferably within 3%. Here, thickness uniformity (%) refers to the smaller the deviation from the average thickness of each region, i.e., the closer the standard deviation is to 0, the better the thickness uniformity.
[0079] [Formula 1]
[0080] Thickness uniformity (%) = [(Standard deviation of average thickness of 5 regions (nm)) / (Average of average thickness of 5 regions (nm))] × 100
[0081] On the other hand, the average thickness of the dry electrode or the average thickness of the sintered electrode as defined in this invention can be determined by a thickness measurement method known as the α step, and known measuring devices for measuring thickness by this method can be used without limitation to measure thickness.
[0082] On the other hand, after electrospraying with the photosensitive electrode composition, and before sintering, a desired electrode pattern can be achieved based on known exposure and development conditions. For example, as exposure and development conditions after electrospraying, the drying temperature after electrospraying can be 50°C to 70°C, and the UV exposure can be 100 mJ to 700 mJ. Furthermore, as the developer, a Na₂CO₃ solution can be used, for example, with a concentration of 0.1 wt% to 4 wt%. And the development time can be 20 seconds to 100 seconds.
[0083] Methods for implementing the invention
[0084] The present invention will be described in more detail through the following embodiments, but the following embodiments should not be construed as limiting the scope of the present invention, but should be construed as helping to understand the present invention.
[0085] <Example 1>
[0086] Nickel powder with an average particle size of 438 nm was prepared by dry plasma. Subsequently, the prepared nickel powder was wet-classified by centrifugation to obtain a conductive metal powder with an average particle size of 147.1 nm, in which particles with a particle size more than twice the average particle size accounted for 15% of the total nickel powder and particles with a particle size less than 0.5 times the average particle size accounted for 18% of the total nickel powder.
[0087] In addition, after preparing BaTiO3 with an average particle size of 155 nm as ceramic powder, it was wet-classified by centrifugation to prepare ceramic powder with an average particle size of 65.8 nm, wherein particles with a particle size more than twice the average particle size account for 10% of the total ceramic powder and particles with a particle size less than 0.5 times the average particle size account for 9% of the total ceramic powder.
[0088] Then, the aforementioned nickel conductive metal powder with adjusted particle size, ceramic powder, and binder resin are mixed in a mixed solvent prepared by mixing dihydroterpineol acetate and ethyl acetate in a 1:1 weight ratio. The binder resin is prepared by mixing polyvinyl butyral with a weight average molecular weight of about 70,000 and ethyl cellulose with a weight average molecular weight of about 40,000 with 100 parts by weight. Specifically, the mixing is carried out such that the weight of ceramic powder is 6.8 parts by weight and the weight of binder resin is 8 parts by weight relative to 100 parts by weight, and the weight of conductive metal powder is 25% by weight in the total composition, thereby preparing an electrode composition for electrospraying with a viscosity of 80 cps at 25°C as shown in Table 1 below.
[0089] At this point, the viscosity of the prepared electrode composition for electro-jet is measured using a Borlefeld rotational viscometer LV according to ISO 554 at 25°C, 65% relative humidity, and 10 rpm.
[0090] <Examples 2 to 14>
[0091] Except for variations in the content of conductive metal powder, average particle size, particle size distribution, content of ceramic powder, average particle size, and / or viscosity of the electrode composition as shown in Table 1 or Table 2 below, the electrode composition for electrospraying was prepared in the same manner as in Example 1.
[0092] At this time, the ceramic powder used is ceramic powder whose particle size is adjusted by wet classification. The ceramic powder has a particle size distribution in which particles with a particle size more than twice the average particle size account for less than 10% of the total ceramic powder and particles with a particle size less than 0.5 times the average particle size account for less than 10% of the total ceramic powder.
[0093] <Comparative Example 1>
[0094] Except for changing the average particle size of the conductive metal powder as shown in Table 1 below, the electrode composition for electro-spraying was prepared in the same manner as in Example 1.
[0095] <Experimental Example 1>
[0096] A ceramic slurry with a viscosity of 300 cps was prepared by including 10 parts by weight of polyvinyl butyral binder resin and butyl carbitol acetate as a solvent, relative to 100 parts by weight of barium titanate ceramic composition. A ceramic green sheet with a thickness of 5 μm was prepared using this slurry. On the above ceramic green sheet, an electrode composition for electro-spraying was electro-sprayed using an electro-spraying device at 18°C and 30% relative humidity. Electro-spraying was performed at a discharge rate of 3 ml / min per orifice, with an air gap of 24 cm between the nozzle and the ceramic green sheet surface, and an applied voltage of 70 kV. This resulted in a thickness of less than 1 μm upon drying, and a distance of less than 200 μm between adjacent electrodes. The dried electrode pattern was then obtained by drying at 100°C for 10 minutes.
[0097] In addition, the ceramic green sheet with the electrode pattern is sintered at 1000°C for 2 hours in an atmospheric atmosphere to achieve the electrode pattern in a sintered state.
[0098] Subsequently, the following physical properties of the electrode patterns in the dry state or in the sintered state were measured, and the results are shown in Table 1 or Table 2 below.
[0099] 1. Average thickness and thickness uniformity
[0100] The average thickness was determined using an Alpha-Step probe surface profiler (Dektak 150, Bruker).
[0101] In addition, the surface of the electrode to be tested is divided into five non-overlapping regions of the same area. The average thickness of each of the five regions is measured, and then the average thickness value and standard deviation of the five electrode regions are calculated. The thickness uniformity is calculated as shown in Equation 1 below.
[0102] [Formula 1]
[0103] Thickness uniformity (%) = [(Standard deviation of average thickness of 5 regions (nm)) / (Average of average thickness of 5 regions (nm))] × 100
[0104] 2. Continuous electrode surface formation
[0105] The dried electrode pattern is observed using an optical microscope. The number of portions where no electrode material has formed is counted and the area is measured. The results are evaluated as 0 to 5 points according to the following criteria.
[0106] - No areas without electrodes formed: 5 points
[0107] - The number of unelectrode portions is 1 to 2, and the area of the unelectrode portions is within 2% of the total observed electrode area: 4 points
[0108] - The number of non-electrode portions is greater than 2 and equal to or less than 5, and the area of the non-electrode portions is within 5% of the total observed electrode area: 3 points
[0109] - The number of non-electrode portions is greater than 5 and equal to or less than 10, and the area of the non-electrode portions is greater than 5% and equal to or less than 10% of the total observed electrode area: 2 points
[0110] - The number of non-electrode portions is greater than 10 and equal to or less than 20, and the area of the non-electrode portions is greater than 5% and equal to or less than 15% of the total observed electrode area: 1 point
[0111] - The number of non-electrode portions is greater than 20 and the area of non-electrode portions is greater than 15% of the total observed electrode area: 0 points
[0112] 3. Relative shrinkage characteristics and thickness uniformity of sintered electrodes
[0113] The shrinkage rate of the prepared sintered electrode pattern was measured. The shrinkage rate of Example 4 was set to 100, and the shrinkage rate of other examples was expressed as a relative percentage.
[0114] At this point, the shrinkage rate is calculated using Equation 2 after measuring the average thickness of the dry electrode and the average thickness of the sintered electrode.
[0115] [Equation 2]
[0116] Shrinkage rate (%) = (Average electrode thickness after sintering (nm) / Average electrode thickness after drying (nm)) × 100
[0117] In addition, as for thickness uniformity, the electrode surface for thickness measurement is divided into five non-overlapping regions, the average thickness of each of the five regions is measured, and then the average thickness value of the five electrode regions and its standard deviation are calculated. The thickness uniformity is calculated according to Equation 1 above.
[0118] In Tables 1 and 2 below, "Ratio A" and "Ratio B" refer to the ratios of particles with a diameter more than twice the average diameter of the conductive metal powder and particles with a diameter less than 0.5 times the average diameter of the conductive metal powder, respectively, in the total amount of conductive metal powder. "Ratio C" is the value obtained by dividing the average diameter of the ceramic powder by the average diameter of the conductive metal powder. Furthermore, the content of conductive metal powder is based on the percentage of the total weight of the electrode composition used for electro-spraying, and the content of ceramic powder is based on the content of 100 parts by weight of conductive metal powder.
[0119] Table 1
[0120]
[0121]
[0122] Table 2
[0123]
[0124] As can be seen from Tables 1 and 2, in the case of the electrode composition of Comparative Example 1 containing conductive metal powder with an average particle size of more than 150 nm, the average thickness of the dry electrode is less than 1.0 μm, but the thickness uniformity is 28.40%, which is very poor. Therefore, it can be seen that the maximum thickness of the dry electrode exceeds 1.0 μm.
[0125] Furthermore, in Examples 1 and 2, which contain conductive metal powder with an average particle size of less than 150 nm, the maximum thickness of the dried electrode formed after electrospraying is less than 1.0 μm. However, in Example 2, particles with a particle size more than twice the average particle size account for 26% of the conductive metal powder, resulting in a large number of coarse particles. This leads to an increase in the settling velocity of the conductive metal powder, resulting in uneven spraying of the conductive metal powder in the solution during electrospraying. Therefore, it can be seen that the continuous electrode surface formation is greatly reduced compared to Example 1.
[0126] On the other hand, in Examples 3 and 4 where the average particle size of the conductive metal powder is less than 100 nm, it can be seen that the average thickness of the dried electrode achieved by electrospraying under the same conditions is thinner than that in Example 1, and the thickness uniformity and continuous electrode surface formation of the dried electrode are increased.
[0127] However, compared to the electrode composition of Example 3, the electrode composition of Example 4 has a lower ratio of particles with a particle size more than twice the average particle size of the conductive metal powder. Therefore, the uniformity of the conductive metal powder content sprayed during electro-spraying is increased. Furthermore, since the ceramic powder is mixed in a manner in which the average particle size relative to the average particle size of the conductive metal powder is further adjusted, the thickness uniformity of the dried electrode, the continuous electrode surface formation, and the shrinkage characteristics and thickness uniformity of the sintered electrode are achieved to be excellent.
[0128] Furthermore, it was found that in Example 6, which mixed ceramic powder with an average particle size less than 0.1 times the average particle size of the conductive metal powder, the thickness uniformity of the dried electrode decreased compared to Example 4, and the shrinkage characteristics and thickness uniformity of the sintered electrode also decreased. Additionally, it was found that in Example 7, which mixed ceramic powder with an average particle size greater than 0.5 times the average particle size of the conductive metal powder, the shrinkage characteristics of the sintered electrode were significantly reduced.
[0129] In addition, when the content of conductive metal powder exceeds 30% by weight, the increased conductivity of the electro-spraying composition affects the electro-spraying, resulting in a reduction in the continuous electrode surface formation compared to Example 4, and a decrease in the thickness uniformity of the dried electrode.
[0130] Furthermore, even in Example 10, where the content of conductive metal powder is less than 10% by weight, it is known that the continuous electrode surface formation and uniformity of drying thickness are reduced compared to Example 9.
[0131] On the other hand, regarding the content of ceramic powder, the shrinkage rate of the sintered electrode in Example 12, where the content of ceramic powder exceeds the preferred range, is greatly increased compared to Example 4, while the conductivity reduction effect in Example 14, where the content of ceramic powder is less than the preferred range, is minimal. It can be seen that the thickness uniformity of the dried electrode is reduced.
[0132] <Example 15>
[0133] Prepared in the same manner as in Example 1, but with the difference that, in order to realize the photosensitive electrode composition for electrospraying, nickel conductive metal powder and ceramic powder with particle size adjusted in Example 1 were mixed in a mixed solvent, which was formed by mixing dihydroterpineol and dihydroterpineol acetate in a 1:1 weight ratio, and a binder resin comprising 75 wt% of an acrylate copolymer copolymer having a weight average molecular weight of about 10,000 and copolymerized from 19.5 mol% methacrylic acid, 38.5 mol% methyl methacrylate and 42 mol% isobornyl methacrylate, and 25 wt% polyvinyl alcohol resin, and relative to 100 parts by weight of light... The photosensitive resin is also mixed with 13 parts by weight of pentaerythritol triacrylate as a multifunctional monomer and azobisisobutyronitrile as a photoinitiator. Specifically, the mixture is mixed such that, relative to 100 parts by weight of conductive metal powder, the weight of ceramic powder is 6.8 parts by weight and the total weight of binder resin and multifunctional monomer is 8 parts by weight, and the weight of photoinitiator is 1 part by weight relative to 100 parts by weight of photosensitive resin. Finally, the weight of conductive metal powder in the total composition is 25% by weight, thereby preparing an electrode composition for electrospraying with a viscosity of 80 cps at 25°C as shown in Table 3 below.
[0134] At this point, the viscosity of the prepared electrode composition for electro-spraying was determined using a Borlefeld rotational viscometer LV according to ISO 554, at a temperature of 25°C, a relative humidity of 65%, and a rotational speed of 10 rpm.
[0135] <Examples 16 to 28>
[0136] Except for variations in the content of conductive metal powder, average particle size, particle size distribution, content of ceramic powder, average particle size, and / or viscosity of the electrode composition as shown in Table 3 or Table 4 below, the electrode composition for electrospraying was prepared in the same manner as in Example 15.
[0137] At this time, the ceramic powder used is ceramic powder whose particle size is adjusted by wet classification. The ceramic powder has a particle size distribution in which particles with a particle size more than twice the average particle size account for less than 10% of the total ceramic powder and particles with a particle size less than 0.5 times the average particle size account for less than 10% of the total ceramic powder.
[0138] <Comparative Example 2>
[0139] Except for changing the average particle size of the conductive metal powder as shown in Table 3 below, the electrode composition for electro-spraying was prepared in the same manner as in Example 15.
[0140] <Experimental Example 2>
[0141] On the ceramic green sheet used in Experimental Example 1, the photosensitive electrode compositions of Examples 15 to 28 and Comparative Example 2 were electrosprayed using an electrospraying device at 18°C and 30% relative humidity. Electrospraying was performed at a discharge rate of 3 ml / min per orifice, with a distance of 24 cm between the nozzle and the surface of the ceramic green sheet, i.e., an air gap, and an applied voltage of 70 kV, so that the thickness was less than 1 μm when dried. Then, the film was dried at 65°C for 10 minutes to achieve a photosensitive electrode layer in a dry state.
[0142] Then, a mask is placed on the aforementioned photosensitive electrode layer to form a predetermined electrode line pattern, and exposed to ultraviolet light with an intensity of 550 mJ. The electrode pattern is then developed for 30 seconds using a developer solution of 3% Na₂CO₃ by weight. Subsequently, the ceramic green sheet with the electrode pattern is sintered at 1000°C for 2 hours in an atmospheric atmosphere to achieve the electrode pattern in a sintered state.
[0143] Subsequently, the following physical properties of the photosensitive electrode layer in a dry state, the electrode pattern after exposure and development, or the sintered electrode pattern were measured, and the results are shown in Table 3 or Table 4 below.
[0144] At this time, the evaluation methods for (1) average thickness and thickness uniformity, (2) continuous electrode surface formation of the dried photosensitive electrode layer, and (3) relative shrinkage characteristics and thickness uniformity of the sintered electrode are the same as those in Experimental Example 1.
[0145] (4) Undercut ratio
[0146] After exposure, cross-sections were cut at any 10 locations on the developed electrode pattern, and SEM images were taken. The upper and lower widths of the electrode cross-sections at each location were measured, and the percentage of the lower width relative to the upper width (lower width (μm) × 100 / upper width (μm)) was calculated, which is the undercut ratio for each location. The average undercut ratio of the 10 locations was then calculated. The closer the undercut ratio is to 100%, the higher the quality of the electrode, indicating that sufficient exposure has been achieved up to the lower side of the electrode.
[0147] Furthermore, in Tables 3 and 4 below, "Ratio A" and "Ratio B" refer to the ratio of particles with a diameter more than twice the average diameter of the conductive metal powder and the ratio of particles with a diameter less than 0.5 times the average diameter of the conductive metal powder, respectively, in the total amount of conductive metal powder. Additionally, "Ratio C" is the value obtained by dividing the average diameter of the ceramic powder by the average diameter of the conductive metal powder. Furthermore, the content of conductive metal powder is based on the content ratio of the total weight of the photosensitive electrode composition used for electro-jetting, and the content of ceramic powder is based on the content of 100 parts by weight of conductive metal powder.
[0148] Table 3
[0149]
[0150]
[0151] Table 4
[0152]
[0153]
[0154] As can be seen from Tables 3 and 4, in the case of the electrode composition of Comparative Example 2 containing conductive metal powder with an average particle size of more than 150 nm, the average thickness of the dry electrode is less than 1.0 μm, but the thickness uniformity is 28.40%, which is very poor. Therefore, it can be seen that the maximum thickness of the dry electrode exceeds 1.0 μm.
[0155] Furthermore, in Examples 15 and 16, which contain conductive metal powder with an average particle size of less than 150 nm, the maximum thickness of the dried electrode formed after electrospraying is less than 1.0 μm. However, in Example 16, 26% of the conductive metal powder has a particle size more than twice the average particle size, resulting in a large number of coarse particles. This leads to an increased settling velocity of the conductive metal powder, resulting in uneven distribution of the conductive metal powder in the sprayed solution during electrospraying. Therefore, the continuous electrode surface formation is significantly reduced compared to Example 15. In addition, it is known that insufficient exposure on the lower side of the electrode leads to severe undercutting, thus deteriorating the quality of the resulting electrode.
[0156] On the other hand, in Examples 17 and 18 where the average particle size of the conductive metal powder is less than 100 nm, it can be seen that the average thickness of the dried electrode achieved by electrospraying under the same conditions is thinner than that in Example 1, and the thickness uniformity and continuous electrode surface formation of the dried electrode are increased.
[0157] However, compared to the electrode composition of Example 17, the electrode composition of Example 18 has a lower ratio of particles with a particle size more than twice the average particle size of the conductive metal powder. Therefore, the uniformity of the conductive metal powder content sprayed during electro-spraying is increased. Furthermore, since the ceramic powder is mixed in a manner in which the average particle size relative to the average particle size of the conductive metal powder is further adjusted, the thickness uniformity of the dried electrode, the continuous electrode surface formation, and the shrinkage characteristics and thickness uniformity of the sintered electrode are achieved to be excellent.
[0158] Furthermore, it was found that in Example 20, which mixed ceramic powder with an average particle size less than 0.1 times the average particle size of the conductive metal powder, the thickness uniformity of the dried electrode decreased compared to Example 18, and the shrinkage characteristics and thickness uniformity of the sintered electrode also decreased. Additionally, it was found that in Example 21, which mixed ceramic powder with an average particle size greater than 0.5 times the average particle size of the conductive metal powder, the shrinkage characteristics of the sintered electrode were significantly reduced.
[0159] Furthermore, when the content of conductive metal powder exceeds 30% by weight, the increased conductivity of the electrospray composition affects electrospraying, resulting in reduced continuous electrode surface formation compared to Example 18, and also reduced uniformity of the dried electrode thickness. In addition, it is known that insufficient exposure of the lower part of the electrode leads to severe undercutting.
[0160] Furthermore, even in Example 24, where the content of conductive metal powder is less than 10% by weight, it is known that the formation of continuous electrode surface and the uniformity of drying thickness are reduced compared to Example 23.
[0161] On the other hand, regarding the content of ceramic powder, the shrinkage rate of the sintered electrode in Example 26, where the content of ceramic powder exceeds the preferred range, is greatly increased compared to Example 18, while the conductivity reduction effect in Example 28, where the content of ceramic powder is less than the preferred range, is minimal. It can be seen that the thickness uniformity of the dried electrode achieved is lower than that in Example 27.
[0162] The above description illustrates one embodiment of the present invention. However, the scope of the present invention is not limited to the embodiments described herein. Those skilled in the art can easily propose other embodiments by adding, modifying, deleting, or adding elements within the same scope, and these fall within the scope of the present invention.
Claims
1. An electrode composition for electro-jetting, characterized in that it is an electrode composition for achieving an electrode with an average thickness of 1.0 μm or less during drying, and wherein... The mixture includes conductive metal powder, ceramic powder, adhesive resin and solvent with an average particle size of less than 150 nm. Among the conductive metal powder, the number of particles with a particle size of more than twice the average particle size is less than 20% of the total number of conductive metal powders, and the number of particles with a particle size of less than 0.5 times the average particle size is less than 20% of the total number of conductive metal powders.
2. The electrode composition for electro-jet injection according to claim 1, characterized in that, The electrode composition described above for electro-jet injection is an electrode composition for realizing the internal electrode of a multilayer ceramic component.
3. The electrode composition for electro-jet injection according to claim 1, characterized in that, The average particle size of the above-mentioned conductive metal powder is less than 80 nm.
4. The electrode composition for electro-jet injection according to claim 1, characterized in that, The aforementioned conductive metal powder includes at least one metal selected from the group consisting of Ni, Mn, Cr, Al, Ag, Cu, Pd, W, Mo, and Co, an alloy containing at least one of them, and a mixed metal containing at least two of them.
5. The electrode composition for electro-jet injection according to claim 1, characterized in that, The ceramic powder has an average particle size that is 0.1 to 0.5 times that of the conductive metal powder.
6. The electrode composition for electro-jet injection according to claim 1, characterized in that, The aforementioned ceramic powder includes at least one ceramic powder selected from the group consisting of titanium dioxide, alumina, silicon dioxide, cordierite, mullite, spinel, barium titanate, calcium zirconium oxide, and zirconium oxide.
7. The electrode composition for electro-jet injection according to claim 1, characterized in that, The content of the aforementioned conductive metal powder is based on a total weight of 10% to 30% by weight.
8. The electrode composition for electro-jet injection according to claim 1, characterized in that, The content of the above-mentioned ceramic powder is 4 to 10 parts by weight relative to 100 parts by weight of conductive metal powder.
9. The electrode composition for electro-jet injection according to claim 1, characterized in that, The content of the above-mentioned adhesive resin is 2 to 13 parts by weight relative to 100 parts by weight of conductive metal powder.
10. The electrode composition for electro-jet injection according to claim 1, characterized in that, The aforementioned adhesive resin comprises 30 to 60 parts by weight of ethyl cellulose relative to 100 parts by weight of polyvinyl butyral.
11. The electrode composition for electro-jet injection according to claim 1, characterized in that, The electrode composition for electro-spraying described above includes a photosensitive resin as a binder resin, and also includes monomers and photoinitiators.
12. The electrode composition for electro-jet injection according to claim 11, characterized in that, The total weight of the above-mentioned adhesive resin and monomer is 2 to 13 parts by weight relative to 100 parts by weight of conductive metal powder.
13. The electrode composition for electro-jet injection according to claim 1, characterized in that, The average particle size of the ceramic powder is less than 45 nm.
14. The electrode composition for electro-jet injection according to claim 1, characterized in that, The viscosity at 25°C is 50 cps to 150 cps.
15. An electro-spraying electrode, which is an electrode dried after electro-spraying an electrode composition for electro-spraying according to any one of claims 1 to 14 onto a predetermined area, characterized in that, It has an average thickness of less than 1.0 μm.
16. The electro-jet electrode according to claim 15, characterized in that, The thickness uniformity is below 10%.
17. A multilayer ceramic component, characterized in that, This includes an internal electrode formed by sintering the electro-injection electrode according to claim 15.
Citation Information
Patent Citations
Process for producing ceramic green sheet
JP2006210820A
Composite film and manufacturing method and manufacturing apparatus of composite film pattern
JP2020152813A
Paste for internal electrode, and manufacturing method of laminate ceramic electronic component
JP2020188111A
